Neurological Abnormalities in Congenital Rubella Syndrome and Possible Pathophysiology - Erny Erny; Okky Prasetyo; Ayli Soekanto (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Congenital rubella syndrome is a disease that is a relative severe health problem because it causes multiorgan disability. The purpose of the study was to describe the neurological abnormallities that occur in congenital rubella syndrome and its pathophysiology.Case Presentation: A descriptive study with the subjects of the study of infants and children with congenital rubella syndrome found in the private practice of pediatricians for 10 years aged 15 years with the most complaints of developmental and growth delays, recurrent seizures and behavioral disorders. most are first children with mothers without Measles, Mumps, and Rubella (MMR) vaccination. Inclusion criteria: infants and children with clinical manifestations of at least 2 of all major clinical signs (hearing loss, congenital cataracts and congenital heart defects) accompanied by evidence of infection in the form of rubellaspecific serum IgM and a history of the mother experiencing infection during pregnancy as evidenced by IgG results and or IgM rubella antibodies.Results: 13 cases were obtained, 92.3% of the case population with multiorgan disability and only 1 case (7.69%) with neurological disorders alone. 84.6% of cases of neurological disability occurred as a result of infection in the 1st trimester.Conclusion: Neurological abnormalities were acquired in the entire study population and were mostly due to infections in the 1st trimester of pregnancy.Keywords: neurological abnormalities, congenital rubella syndrome.Correspondence: Erny. Pediatric Department Medical Faculty Wijayakusuma University. Jl. Dukuh Kupang XXV no 54 Surabaya, East Java, Indonesia. Email: drernyspa@gmail.com. Mobile: 0818381740.Indonesian Journal of Medicine (2022), 07(04): 449-455https://doi.org/10.26911/theijmed.2022.07.04.10